Strategi Konten Digital Islami dalam Meningkatkan Brand Awareness Toko Tayyiba melalui Media Sosial Instagram - Naufal Ahmad Alfian; Nieldya Nofandrilla (Universitas Medan Area, 2026)
This descriptive qualitative study evaluates the Islamic digital content strategy of Toko Tayyiba’s Instagram account in Surakarta and its impact on brand awareness. Data were collected in August 2025 through semi‑structured interviews with six informants (three active followers and three internal actors: supervisor, social media specialist, and content creator), complemented by post observations and account documentation. The analysis followed Miles’ cycle of data reduction, display, and conclusion drawing, validated through source, method, and time triangulation. Findings indicate that the consistency of Islamic identity through hijab‑wearing models and subtle Mekkah elements, combined with the application of visual hooks in the first seconds of content and entertainment‑based local comedy, successfully increased organic reach, engagement, familiarity, and strengthened Brand recognition, Brand Recall, and even Top Of Mind positioning among audiences. However, the effectiveness of this strategy remains partial due to weaknesses in product education and catalog content, including limited research depth, insufficient product details (origin, benefits, usage guidance, price transparency), and inconsistent feed aesthetics, which hinder the transition from awareness and engagement to purchase intention and sales conversion.